Morfofisiologia de jundiás sedados ou anestesiados com MS222, óleo essencial de Aloysia triphylla e propofol - Gressler, Luciane Tourem (2016)
One of the pillars for optimizing cultured fish handling is stress reduction, and sedatives and anesthetics are tools usually employed in order to reach such goal. However, these drugs may cause physiological changes that can be deleterious to the animal if surpassing a physiological threshold. In this context, the current work investigated the use of a substance of natural origin, the essential oil (EO) of Aloysia triphylla, as well as of two synthetic drugs, tricaine methanesulfonate (MS222) and propofol, in silver catfish (Rhamdia quelen). The trials involved anesthesia (EO and MS222), for application in intensive or invasive manipulations, and sedation (propofol), to be used in procedures such as fish transport. Analyses of the effects of MS222, the prototypical fish anesthetic, and of the EO of A. triphylla showed that anesthesia with the naturally occurring substance presented more benefits for it prevented lipoperoxidation and limited cortisol secretion and ionic loss, although induction and recovery times were shorter with the traditional drug. Propofol as sedative for up to 12 hours did not increase cortisol secretion and alterations observed in hematological, biochemical and hydromineral indexes were limited. Moreover, assessment of gill morphology indicated that ionregulation and ventilation were not affected by propofol, while oxidative stress markers evidenced absence of peroxidative damage in vital organs, brain and liver, due to induction of some components of the antioxidant system, specially the enzyme superoxide dismutase, in the presence of the drug. These findings indicate that the EO of A. triphylla and propofol represent promising alternatives to be used in Brazilian fish culture, since anesthetics routinely applied in fish in other countries, such as MS222, are not commercially available in Brazil. In addition, the performance of MS222 was inferior when compared to that of the EO, which demonstrates that short induction and recovery periods do not necessarily mean less physiological burden. Studies as the ones described in this work contribute to welfare preservation of captive animal since possible actions to reduce stress are suggested.